THE DIFFERENCES OF THE EFFECT OF EXERCISE METHODS AND LIMB MUSCLE POWER ON THE ABILITY OF 100 METERS SPRINT - Habib Kuncoro, Ardyan; Priya Budi S, Nurruddin; Danardono, Hajar (Journal Of Indonesia Sport Education and Adapted Physical Education (JISEAPE), 2021)
The aims of this study were to determine: (1) whether or not there were the differences of the effect of drill training versus game training on the ability of seventh grade female students of SMPIT Darussalam Tanon Sragen in the 2020/2021 school year. (2) Whether or not there were differences of the ability to run 100 meters sprint in female students of class VII SMP IT Darussalam Tanon Sragen in the 2020/2021 school year between students with high leg muscle power and students with low leg muscle power. (3) Whether or not there was an interaction between exercise methode and leg muscle power on the ability of class VII female SMPIT Darussalam Tanon Sragen students to have 100 meters sprint in the 2020/2021 school year.This study employed a 2 X 2 factorial design experimental method. The population and sample in this study were 60 female students in grade VII SMP IT Darussalam Tanon Sragen for the academic year 2020/2021. The results of the leg muscle power test were used to group the research samples. The test results of leg muscle power were classified into three categories: high leg muscle power, moderate leg muscle power, and low leg muscle power. The samples used were 20 people with high leg muscle power criteria and 20 people with low leg muscle power criteria, with the moderate leg muscle power criteria omitted. Data was collected using leg muscle power tests, specifically the standing broad jump test and the 100-meter sprint test. The data was analyzed using 2 X 2 ANOVA, then Newman-Keuls.The findings show: (1) there is a significant difference of the effect of the drill training methods and the game training method on the ability to have 100 meters sprint in class VII female students of SMPIT Darussalam Tanon Sragen in the academic year 2020/2021. The data analysis shows Fo = 6.817 > Ftable 5% 5% 4.11. (2) There is a significant difference in the ability to have 100 meters sprint between students with high leg muscle power and students with low leg muscle power in female students of class VII SMP IT Darussalam Tanon Sragen in the 2020/2021 school year. (3) There is an interaction between exercise methode and leg muscle power on the ability to have 100 meters sprint in class VII female students of SMPIT Darussalam Tanon Sragen in the 2020/2021 school year. The results of data analysis shows that Fcount = 4.868 > Ftable 5% = 4.11. The level of leg muscle power possessed by female students of class VII SMP IT Darussalam Tanon Sragen in the 2020/2021 academic year has an effect on the 100-meter sprint exercise.